Investigation of heat transfer enhancement in an annular conduit with angled fins using functionalized GNP colloidal suspension. Issue 1 (December 2021) - Nair, Sayshar Ram; Oon, Cheen Sean; Tan, Ming Kwang; Kazi, S.N.
Abstract: Heat exchangers are important equipment with various industrial applications such as power plants, HVAC industry and chemical industries. Various fluids that are used as working fluid in the heat exchangers such as water, oil, and ethylene glycol. Researchers have conducted various studies and investigations to improve the heat exchanger be it from material or heat transfer point of view. There have been attempts to create mixtures with solid particles suspended. This invention had some drawbacks since the pressure drop was compromised, on top of the occurrence of sedimentation or even erosion, which incurs higher maintenance costs. A new class of colloidal suspension fluid that met the demands and characteristics of a heat exchanger was then created. This novel colloidal suspension mixture was then and now addressed as "nanofluid". In this study, the usage of functionalized graphene nanoplatelet (GNP) nanofluids will be studied for its thermal conductivity within an annular conduit with angled fins, which encourage swirling flows. The simulation results for the chosen GNP nanofluid concentrations have shown an enhancement in thermal conductivity and heat transfer coefficient compared to the corresponding base fluid thermal properties. The data from this research is useful in industrial applications which involve heat exchangers with finned tubes.